Studi Literatur: STEM untuk Menumbuhkan Keterampilan Abad 21 di Sekolah Dasar - Susi Hermin Rusminati; Triman Juniarso (Journal on Education, 2023)
Education is the main foundation of a country. The use of STEM in learning is an effort made so that students can apply 21st century skills. This study aims to examine and explore the application of STEM in learning and its impact on 21st century skills. The method used in this study is a systematic literature study and in accordance with the discussion, namely about STEM and 21st century skills. Based on the results of a systematic review of literature, STEM learning design can be used as an acternative by teachers in carrying out the learning process so that it can meet 21st century skills, namely critical thinking and problem solving, creative thinking, communication, and collaboration.